POETRY IN EFL CLASSROOM - Antika, Rindilla (TELL - US JOURNAL, 2016)
Literature is considered as a promoting tool for language learning purposes.  Literature can be used to foster students motivation to read and write in order to achieve their academic proficiency. Poetry as a part of literature has affirmed that literature has a great deal in developed students’ literacy competence. This paper argues for the use of literature and some approaches in teaching and learning literature especially poetry in EFL classroom. This paper also elaborates some benefits of using literature and poetry in the EFL classroom and proposes some assessments which can be used to assess students’ literary competence in poetry.